The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/app10238651
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning-Based Timing Offset Estimation for Deep-Sea Vertical Underwater Acoustic Communications

Abstract: This study proposes a novel receiver structure for underwater vertical acoustic communication in which the bias in the correlation-based estimation for the timing offset is learned and then estimated by a deep neural network (DNN) to an accuracy that renders subsequent use of equalizers unnecessary. For a duration of 7 s, 15 timing offsets of the linear frequency modulation (LFM) signals obtained by the correlation were fed into the DNN. The model was based on the Pierson–Moskowitz (PM) random surface height m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…In the important work by Wu et al, 18 the authors introduce a DL system for timing offset estimation particularly for deep sea vertical underwater communication. Here, this idea is useful because there are a lot of unknowns in the ocean channel and it is shown that the method gives good performance in timing offset estimation.…”
Section: Frequency Phase and Symbol Synchronizationmentioning
confidence: 99%
“…In the important work by Wu et al, 18 the authors introduce a DL system for timing offset estimation particularly for deep sea vertical underwater communication. Here, this idea is useful because there are a lot of unknowns in the ocean channel and it is shown that the method gives good performance in timing offset estimation.…”
Section: Frequency Phase and Symbol Synchronizationmentioning
confidence: 99%
“…It cannot be denied that by mining big data, machine learning (ML) or AI play a very important role in handling these two problems [15]. However, in order to have diverse measurement results, most of recent studies use channel modeling, instead of having actual measurement results [16], [17].…”
Section: Introductionmentioning
confidence: 99%